Edukasi Bahaya Pinjaman Online Ilegal bagi Santri - Purwatiningsih Purwatiningsih; Lyandra Aisyah Margie; Silvia Sari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Financial literacy is an individual's knowledge and expertise related to finances that influences economic behavior in making decisions about financial management. Low financial literacy can lead to overspending, increasing debt burdens, difficulty saving, and vulnerability to investment fraud and illegal online loans. Islamic boarding school students are generally unaware of the constant threat of digital financial crimes, such as illegal online loans. Based on this situation, one way to help them avoid the dangers of illegal online loans is by providing education regarding the dangers of illegal online loans. The goal of this education is to increase their financial awareness and literacy to prevent them from being trapped by illegal online loans that are detrimental, and to equip them with the skills to manage their finances healthily and responsibly. This education is important to protect students from negative impacts such as high interest rates, multiple fines, intimidating debt collection, and serious financial, psychological, and legal consequences. The community service team uses a three-stage educational method: lecture, discussion, and evaluation. The community service took place at the RH La Tahzan Islamic Boarding School, Cinangka Village, Sawangan District, Depok City, West Java Province on August 10, 2025, with 30 students participating. The result of this education is an increased understanding of the students about the dangers of online loans, especially those that are illegal and not supervised by the Financial Services Authority (OJK). This is demonstrated by the beginning of the formation of a habitual process in managing personal finances, keeping personal data safe and being more careful when opening links from unknown sources.